Policymaker perceptions of COVID-19 impacts, opportunities and challenges for sustainable wildlife farm management in Vietnam - Pham, T.T.; Tang, T.K.H.; Dang, H.P.; Nguyen, T.K.N.; Hoang, T.L.; Tran, N.M.H.; Nguyen, T.T.A.; Nguyen, T.V.A.; Valencia, I. (Elsevier, 2022)
This paper uses Vietnam – where overexploitation of wildlife resources is a major threat to biodiversity conservation – as a case study to examine how government officials perceive the impacts of COVID-19 on wildlife farming, as well as the opportunities and challenges presented for sustainable wildlife management. Findings show Vietnamese government officials perceive COVID-19 to have had mixed impacts on wildlife conservation policies and practice. While the pandemic strengthened the legal framework on wildlife conservation, implementation and outcomes have been poor, as existing policies are unclear, contradictory, and poorly enforced. Our paper also shows policymakers in Vietnam are not in favor of banning wildlife trade. As our paper documents the immediate impacts of the pandemic on wildlife farming, more research is necessary to analyse longer-term impacts.